482 A CASE OF RIGHT SIDE INFECTIVE ENDOCARDITIS IN PATIENT WITH VENTRICULAR SEPTAL DEFECT. (15th December 2022) - Bruno, Noemi; Grieco, Martina; Galea, Nicola; Tanzilli, Gaetano; Torromeo, Concetta
Abstract: A 25-years old white female was admitted to our emergency department presenting with dyspnea, fever, cough and nausea. Her medical background included a small ventricular septal defect (VSD) (congenital) with a left to right shunt, micropolicistic ovary syndrome, Sars Cov 2 infection on January 2022, history of cutaneous infection after sternal piercing in the last three years. Patient showed onset of fever, headache and nausea since 20 days and had a history of ampicillin and cephalosporin usage for 15 days for comunitary pneumonia. Upon arrival in the emergency room, physical examination revealed temperature 38°C, crackles on down right lung fields, regular but tachycardic rhythm, 3/6 holosystolic murmur in the third left intercostal space, also skin redness around the piercing zone. Laboratory test showed increasing of WB (white blood cells), C-reactive protein (CPR) and procalcitonin. Because of worsening of respiratory conditions, CT chest was performed, showing tree in bud sign, with pulmonary pattern suggestive of staphylococcal "emboligenous-like" infectious state. According to patient's clinical history and CT results, she was referred to transthoracic echocardiogram (TTE) demonstrating the presence, on the right side of the small VSD, of a isoechoic large mass (20x 13 mm) with irregular margins attached to the right ventricular wall near the ostium of the VSD, compatible with vegetation; septal tricuspid valve leaflet involvement could not be ruled out. Methicillin-susceptible Staphylococcus aureus (MSSA) was detected six times from blood cultures; therapy with oxacillin 2 gr every 4 hours combined with daptomycin 750 mg daily was started. Cardiac MRI performed after few days, documented the infective involvement of the ventricular and atrial side of the septal leaflet with moderate tricuspid regurgitation (TR). Congenital heart disease (especially Tetralogy of Fallot, bicuspid aortic valve, aortic coarctation, ventricular septal defect) is a lifelong risk factor for infective endocarditis (IE). Size of VSD is generally not correlated with IE that is directly correlated with turbulent flow; tricuspid valve involvement is mostly seen in VSD, often complicated by pulmonary embolism. In this predisposing situation, skin infection of the piercing zone could have caused transient bacteremia which led to the formation of vegetations in the highest turbulence flow zone.